Gambaran Forgiveness pada Siswi SMA korban Bullying - Mikaela Berliyana Alitani; Yeny Duriana Wijaya; Hana Sulistiana (Mathematics Education Study Program, 2025)
Bullying is an behavior that can hurt everybody. So not all the victims can forgive the perpetrator. Forgiveness is a decrease in motivation to take revenge, make distance or avoid the perpetrator. Forgiveness has a positive impact, that contributing to helping teenagers overcome the negative psychological impacts of bullying and encouraging healthy adaptability during their growth phase. However, not all students can forgive the perpetrator. Especially in female students. This happens because female tend to find it more difficult to forgive because female use or utilize feelings more as a medium of manipulation to control themselves. For this reason, this research aims to provide an overview of Forgiveness in female students who are bullied. This type of research is descriptive research with sampling techniques using random sampling techniques involving 100 female students. aged 15 to 20 years who have bullied. The results of this research show that Forgiveness in female students is 58% in the high category and 42% in the low category.